2011
DOI: 10.1097/hjh.0b013e32834cfcf4
|View full text |Cite
|
Sign up to set email alerts
|

Transient renin–angiotensin system stimulation in an early stage of life causes sustained hypertension in rats

Abstract: Transient RAS stimulation causes sustained elevation in BP in young, but not in adult Cyp1a1-Ren2 transgenic rats and is associated with irreversible changes in renal structure and function and a moderate renal inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Prolonged activation of the RAS in Cyp1a1Ren2 rats causes hypertension, increased renal vascular resistance (as measured by flow probe), glomerulosclerosis and tubulointerstitial inflammation (Heijnen et al . , ). In addition, in Cyp1a1Ren2 rats, the kidney seems to be more at risk of development of injury than the heart, which showed only relatively mild maladaptation (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged activation of the RAS in Cyp1a1Ren2 rats causes hypertension, increased renal vascular resistance (as measured by flow probe), glomerulosclerosis and tubulointerstitial inflammation (Heijnen et al . , ). In addition, in Cyp1a1Ren2 rats, the kidney seems to be more at risk of development of injury than the heart, which showed only relatively mild maladaptation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This model is known to develop inducible AngII‐dependent hypertension and ultimately CKD when renin activation is prolonged for 4 weeks or more (Heijnen et al . , , ). We determined whether renal cortical hypoxia is an early event in this process and whether it can be reversed by AT 1 R blockade (Heijnen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the long-lasting BP change in young IHR is due to irreversible renal damage following mRen2 activation. 5,6 Perspectives In IHR, mRen2 gene-related malignant hypertension induces fully reversible myocardial concentric hypertrophy with characteristics of diastolic heart failure, whereas in the related TGR strain systolic heart failure develops. Despite marked LV concentric hypertrophy and reduced stroke volume, the absence of interstitial fibrosis and inflammation may make the IHR model not a true diastolic failure model but rather a model with benign reversible hypertrophy.…”
Section: Several Factors May Have Contributed To the Characteristic Cmentioning
confidence: 99%
“…Using this approach it was shown that transient RAS-stimulation induced sustained hypertension in young, but not adult IHR. 5,6 Most studies in IHR have been focusing on the kidney 5,7,8 and thus information on the cardiac remodeling processes in this model is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, most studies using this model focus on acute hypertension, with few data in terms of chronic hypertension. 13,15,30,31 We therefore aimed to outline the breeding performance and productivity of transgenic Cyp1a1-Ren2 rats, demonstrate the inducible and reversible dose-dependent hypertension in this model, and describe the effect of chronic dosing with I3C on inducible hypertension.…”
mentioning
confidence: 99%